Analisis Manajemen Risiko Pada Proses Produksi Tas Menggunakan Metode Hazard Identification, Risk Assessment And Risk Control (HIRARC) - Ahmad Taqqiyuddin; Mochammad Nuruddin; Deny Andesta (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
The field of occupational safety and health is something that must be considered, because it affects the development, increased production and achievement of zero accidents in the company. UD. Suci Konveksi is one of the small and medium-sized industrial businesses with output in the form of bag products that have been established since 2006. Observations show that the lack of employee awareness in applying OHS to standard operating procedures (SOPs) in force has resulted in several work accidents leading to accidents in machine-based production areas. The purpose of this service activity is to analyze risk management and find out the application of hazard identification, risk assessment and risk control methods (HIRARC) to the bag production process at UD Suci Convection. The results of hazard identification also found there were 11 potential hazards, with the division of 3 potential dangers of low risk entry, 4 potential dangers of entering moderate risk, 2 potential dangers of entering high risk and 2 potential dangers of entering extreme risk. The risk control recommendation is given to the overall potential hazards in UD Suci Convection to prevent repeated work accidents.